2019
DOI: 10.3390/s19143039
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Continuous Turbidity Monitor

Abstract: Turbidity describes the cloudiness, or clarity, of a liquid. It is a principal indicator of water quality, sensitive to any suspended solids present. Prior work has identified the lack of low-cost turbidity monitoring as a significant hurdle to overcome to improve water quality in many domains, especially in the developing world. Low-cost hand-held benchtop meters have been proposed. This work adapts and verifies the technology for continuous monitoring. Lab tests show the low-cost continuous monitor can achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Several novel turbidity sensors have been documented in peer-reviewed literature. Gillett 38 investigated the use of low-cost, commercially-available appliance turbidity sensors (such as those found in washing machines and dishwashers). These sensors work on the principle of light attenuation, where the light detector is placed 180 o from the incident light.…”
Section: State-of-the-art In Low-cost Turbidity Sensingmentioning
confidence: 99%
“…Several novel turbidity sensors have been documented in peer-reviewed literature. Gillett 38 investigated the use of low-cost, commercially-available appliance turbidity sensors (such as those found in washing machines and dishwashers). These sensors work on the principle of light attenuation, where the light detector is placed 180 o from the incident light.…”
Section: State-of-the-art In Low-cost Turbidity Sensingmentioning
confidence: 99%
“…For such applications, distributed wireless sensor networks are required to monitor the parameters over a larger area and send the data monitored to a centralized controller using wireless communication. Such applications normally monitor parameters such as chlorophyll [9], dissolved oxygen concentration [14][15] [16], turbidity [17], PH [18] and temperature [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, different sensors mounted on different platforms (e.g., fluorimeters mounted on buoys) or on probes (e.g., CTD -conductivity, temperature, and depth) are used to provide continuous real-time information on water quality parameters (e.g., [24][25][26]). In addition, in recent years, different studies showed the possibility to use in situ radiometric sensors to characterize water quality status and its temporal variability by means of continuous measurements (e.g., [27,28]).…”
Section: Introductionmentioning
confidence: 99%